Beyond the closet? The trends and visibility of homosexuality coverage in Malaysian newspapers, 1998 – 2012 - Syamsul Zahri Subir (Penerbit Universiti Kebangsaan Malaysia, 2019)
Homosexuality issues in Malaysia started to gain considerable attention from the mainstream news media after the political dispute of Anwar Ibrahim and his sodomy allegation in 1998. Since then, the topic of homosexuality was discussed widely in the news media and it has given the public a medium to communicate and popularize homosexuality in the country. However, there is a relatively little study that investigates homosexuality issue specifically on their trends and pattern in the Malaysian newspaper. This study attempt to track and analyse the trend and visibility of the homosexuality coverage from the Malaysian newspapers particularly from the controlled and government-oriented newspapers of Utusan Malaysia and Berita Harian. This study employed content analysis study to frame the textual evidence of emerging trends on homosexuality for the fifteen years of study, from 1998 to 2012 which was reported in the newspapers. The result revealed that there is a growing visibility of homosexuality issues in the Malaysian newspapers with socio-cultural-political aspects that have some degree of influence on how issues about homosexuality were narrated in the newspaper. The result also subtly reflected the ongoing influence of control by the dominant Malay political hegemony in the country. This study contributes to the knowledge on the understanding of the news media’s role in shaping the parameters of public debate on such a controversial issue within the democratic and cultural politics in the country.